2008
DOI: 10.1021/ja805977f
|View full text |Cite
|
Sign up to set email alerts
|

Diamond-Based Molecular Platform for Photoelectrochemistry

Abstract: Boron doped diamond (BDD) thin film was found to exhibit higher photocurrent conversion efficiencies and photostability compared to commonly used transparent conducting oxides (ITO and FTO) owing to the matching energy levels and strong C-C bonding at the organic/diamond interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 9 publications
4
60
0
Order By: Relevance
“…16 Post-modification of the diamond surface with (other) organic moieties can then be carried out employing various efficient chemical reactions. 14,15,[17][18][19] The first report on dye sensitization of p-type semiconductive diamond electrodes was published in 1999 by Fujishima et al 20 Photocurrent was observed when a synthetic semiconductive p-type diamond electrode was photosensitized by the Ru(bpy) 3 2+ (bpy = 2,2'-bipyridine) molecule in an electrolyte solution. More recently, robust covalent linking of Ru(tpy) 2 (tpy = 2,2':6',2"-terpyridine) dye molecules onto a boron-doped diamond (BDD) surface has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…16 Post-modification of the diamond surface with (other) organic moieties can then be carried out employing various efficient chemical reactions. 14,15,[17][18][19] The first report on dye sensitization of p-type semiconductive diamond electrodes was published in 1999 by Fujishima et al 20 Photocurrent was observed when a synthetic semiconductive p-type diamond electrode was photosensitized by the Ru(bpy) 3 2+ (bpy = 2,2'-bipyridine) molecule in an electrolyte solution. More recently, robust covalent linking of Ru(tpy) 2 (tpy = 2,2':6',2"-terpyridine) dye molecules onto a boron-doped diamond (BDD) surface has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…recombination of the electrons is lower compared to that of conventional semiconductors [12]. Thus, this excess of electrons in the conduction band enhances the Cu deposition.…”
Section: Accepted M Manuscriptmentioning
confidence: 95%
“…Zhong et al [12] studied the photoelectrochemical diamond efficiency and discussed its superior performance compared to other semiconductors in the process of functionalization with bithiophenedicyano molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the BDD is a semiconductor with a wide band gap. This process is improved due to this large band gap, where the recombination of the electrons is lower compared to that of conventional semiconductors [14]. In this way, this excess of electrons enhanced the Cu deposition.…”
Section: Copper Particles Photoelectrodepositionmentioning
confidence: 99%